The Effects of Cultural Restraint on Social Media Motivation, Relationship Benefits, and Relationship Commitment among Young Adults in Jordan: A Conceptual Study - Hatamleh, Islam Habis Mohammad; Zolkepli, Izzal Asnira; Ahmad, Jamilah (IJICC, 2020)
Aim: This paper studies the effects of cultural restraint on social media motivation, relationship commitment, and relationship benefits among young adults in Jordan. Material and methods: This paper is based on a review of the literature and takes a conceptual approach. It suggests the framework for examining social media motivation, relationship benefits and trust among young Jordanian adults, while focusing on the moderating effects of cultural restraint on online relationship commitment. Findings: It was expected that the findings would build on the significance of integrating social media motivation, relationship benefits, cultural restraint, and online relationship commitment among young adults in Jordan, as social media appears to be the main element of dedication to online relationships. Implications: Due to Jordan’s social media engagement radically improving in recent years, it is urged that the impact of its motivation on relationship commitment is conducted, to prevent adverse effects. Young adults are the most important segment of society. Therefore, understanding the benefits and harms of their online relationship commitment to social media motivation is essential. Novelty: To date, no studies examine the effects of cultural restraint on social media motivation, relationship benefits, and relationship commitment among young adults in Jordan. Furthermore, this study will help university students understand their online relationship commitment, as to the benefits or harms of social media motivation.